INTERACTIONS BETWEEN C6H4(CH2NH3)2[PhCO2]2, Et2NH2[Ph(OH)CO2] AND CuCl2, ErCl3 or SnPh3OH: AN INFRARED STUDY - ASSANE TOURE; LIBASSE DIOP (Journal of Engineering Studies and Research)
The interactions of benzoic or salycilic acids salts with di-, trihalides or SnPh3OH have yielded four new complexes and adducts studied by infrared.The suggested structures are discrete or of infinite chain type, the anion behaving as monodentate and hydrogen bonding involved, or bidentate, the environments around the metallic centres being tetrahedral, octahedral or trigonal bipyramidal. When N-H groups are involved in extra hydrogen bonding, a supramolecular architecture may be obtained.